2019
DOI: 10.1039/c9ra06592j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the adsorption capability of areca leaf biochar for methylene blue by K2FeO4-catalyzed oxidative pyrolysis at low temperature

Abstract: A K2FeO4-catalyzed pyrolysis was developed for improving the adsorption capability of areca leaf biochar for methylene blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Table 1 shows the adsorption properties for cationic dye uptake onto unmodified biochars. MG [99][100][101][102][103], MB [104][105][106][107][108][109], rhodamine B (Rh B) [99], basic red 9 (BR 9), and CV [103,110] values are included in the data. Many citations only present the quantity of dye removed (in %) [99,100,104,106,110,111], which is valuable, however, this value varies with adsorbent quantity, dye concentration, and adsorbate volume.…”
Section: Biochar As a Dye Removal Adsorbentmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the adsorption properties for cationic dye uptake onto unmodified biochars. MG [99][100][101][102][103], MB [104][105][106][107][108][109], rhodamine B (Rh B) [99], basic red 9 (BR 9), and CV [103,110] values are included in the data. Many citations only present the quantity of dye removed (in %) [99,100,104,106,110,111], which is valuable, however, this value varies with adsorbent quantity, dye concentration, and adsorbate volume.…”
Section: Biochar As a Dye Removal Adsorbentmentioning
confidence: 99%
“…MG [99][100][101][102][103], MB [104][105][106][107][108][109], rhodamine B (Rh B) [99], basic red 9 (BR 9), and CV [103,110] values are included in the data. Many citations only present the quantity of dye removed (in %) [99,100,104,106,110,111], which is valuable, however, this value varies with adsorbent quantity, dye concentration, and adsorbate volume. MB adsorption capacities (Table 1) are 110, 150, 38, and 195 mg/g for biochar materials derived from microalgae [105], Wodyetia [107], and switchgrass at 873 and 1173 K [45,108], respectively.…”
Section: Biochar As a Dye Removal Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…Balonek et al demonstrated that with the addition of Pt/α-Al 2 O 3 sphere catalyst, the oxidative pyrolysis of cellulose in a fixed bed reactor could run autothermally to produce high yields of bio-oil with no observable char formation. More recently, Yin et al , introduced K 2 FeO 4 to the pomelo peel pyrolysis process to produce magnetic biochar. They claimed that K 2 FeO 4 could not only be the precursor of magnetic iron oxide but also an internal oxidative modifier due to its strong oxidizing capability.…”
Section: Concept Of Autothermal Pyrolysis Of Biomassmentioning
confidence: 99%
“…The presence of dyes in water bodies poses a major threat to human health and aquatic organisms. Methylene Blue (MB) is an organic dye that has been widely used in printing industries for coloring paper, clothes, and plastics [1][2][3]; however, its improper disposal in the environment can cause a series of problems for the environment and human health due to its potential mutagenic and carcinogenic effect and great ability to color ecosystems [4,5].…”
Section: Introductionmentioning
confidence: 99%